Energy Self-Sufficiency: An Economic Evaluation - M.I.T. Energy Laboratory Policy Study Group; AEI National Energy Project (Washington: American Enterprise Institute for Public Policy Research, 1974)
The United States is dedicated to a policy of independence from foreign sources of energy. Under the name "project independence", goals have been set which call for making the nation invulnerable to oil embargoes or price increases in the world petroleum market. Howbeit, in recent months, the feasibility of this particular objective has been called into question; the Federal Energy Administration (FEA) is attempting to formulate an operational definition of "independence" and develop a set of measures to achieve it. This study seeks to contribute to discussion of this issue by evaluating the economic implications of an attempt to achieve self-sufficiency in this critical commodity.
"Earlier version of this study was published in the May 1974 issue of Technology review."
Includes bibliographical references.
ne 24/04/2018
Loans
Keywords: Energy Policy; Power Resources